2019
DOI: 10.3390/f10030211
|View full text |Cite
|
Sign up to set email alerts
|

Water Yield Responses to Gradual Changes in Forest Structure and Species Composition in a Subboreal Watershed in Northeastern China

Abstract: Relationships between forest cover and streamflow have been studied worldwide, but only a few studies have examined how gradual changes in forest structure and species composition due to logging and climate change affect watershed water yield (Q) and flow regimes. In this study, we analyzed long-term (45 years) hydrologic, climate and forest dynamics data from the subboreal Tahe watershed in northeastern China. Our purpose was to evaluate the effects of forest logging and regeneration on changes in forest biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 63 publications
0
18
1
Order By: Relevance
“…Shifts in species composition and structural changes in forests may also strongly influence water yield and flow regimes. A study in Tahe watershed, China observed that as young larch trees and secondary birch forests replaced old‐growth larch forests, there was a reduction in mean annual streamflow along with an increase in the magnitude of high/low flows (Yu et al, 2019). On a similar note, Singh and Mishra (2014) studied water quality amongst four watersheds with different forest profiles of old forests (primary forest, mature secondary forest, and undisturbed mature plantations) open and disturbed forests in the Western Ghats, India.…”
Section: Forest and Watermentioning
confidence: 99%
See 2 more Smart Citations
“…Shifts in species composition and structural changes in forests may also strongly influence water yield and flow regimes. A study in Tahe watershed, China observed that as young larch trees and secondary birch forests replaced old‐growth larch forests, there was a reduction in mean annual streamflow along with an increase in the magnitude of high/low flows (Yu et al, 2019). On a similar note, Singh and Mishra (2014) studied water quality amongst four watersheds with different forest profiles of old forests (primary forest, mature secondary forest, and undisturbed mature plantations) open and disturbed forests in the Western Ghats, India.…”
Section: Forest and Watermentioning
confidence: 99%
“…A decrease in forest cover led to an increase in turbidity, total suspended solids (TSSs), and increased number of Escherichia coli . Moreover, old forests were more effective in reducing turbidity and TSS than disturbed forests (Singh & Mishra, 2014; Yu et al, 2019) as old‐growth forests have a vegetative design that minimizes soil erosion and sediment runoff while promoting soils that provide natural filtration. Therefore, the conservation of old/mature forests is an essential factor for the stabilization of water yield and quality.…”
Section: Forest and Watermentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, in the Upper Grosse Ohe catchment, a 30% of forest loss caused a significant rise in the magnitude of low flows [28]. Yu et al [29] also found deforestation increased the magnitude of low flows in the Tahe River watershed, China, while reforestation had the opposite result. The increment in the magnitude of low flows after deforestation is mainly associated with the reduction of evapotranspiration [30][31][32].…”
Section: Introductionmentioning
confidence: 98%
“…As a result of large-scale fire and logging, the natural secondary forests are widely distributed [34]. Betula platyphylla, as a pioneer species, is the widely distributed natural secondary forest in this region, which accounts for 41.15% and 41.59% of the total forest area and the total forest stock, respectively [35,36]. There are few Betula platyphylla stands older than 80 years, because old Betula platyphylla forests are generally replaced by Larix gmelinii and mixed deciduous forests as a stand successional pathway in this region [37,38].…”
Section: Introductionmentioning
confidence: 99%